Analisa Jam Perawatan Langsung Pada Pasien Bedah Di Ruang Cendrawasih I - Kartika, Dewi -; -, Erwin -; Lestari, Widia - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was to describe direct care hours for patient that admitted on medical surgery ward Cendrawasih I. In this study, researcher uses descriptive design that was conducted at Arifin Achmad Hospital, Riau Province. The number of respondent was 44 choosen by purposive sampling technique. The instrument was observation sheet. The data were analyzed by univariate analysis. The results showed that the average hours of direct care observed for 3 days was 60.32 minutes. Based on the result, nurses should increase care hours and types of care which can also increase the quality of medical surgery ward Cendrawasih I. Keywords :direct care hours, operating room Bibliography : 22 (2004-2013)